Adverse drug reaction related to drug shortage: A retrospective study on the French National Pharmacovigilance Database. Issue 3 (19th October 2022) - Bourneau‐Martin, Delphine; Babin, Marina; Grandvuillemin, Aurélie; Mullet, Charlotte; Salvo, Francesco; Singier, Allison; Cellier, Morgane; Fresse, Audrey; de Canecaude, Claire; Pietri, Tessa; Drablier, Guillaume; Geniaux, Hélène; et al.
Abstract : Aim: Drug shortages are a growing global health issue. The aim of the study was to evaluate the consequences of drug shortages on patient safety based on data recorded in the French National Pharmacovigilance Database. Methods: All cases involving drug shortages reported from 1985 to the end of 2019 were extracted from the database. Results: Following the selection process, 462 cases were included. The number of cases increased significantly from 2004 to 2019. Cases mainly involved drugs from the nervous system (22.1%, 95% confidence interval [CI] 17.5–27.0%), the cardiovascular system (16.4%, 95% CI 11.9–21.4%) and anti‐infectives for systemic use (14.3%, 95% CI 9.7–19.2%) ATC classes. Most of the cases reported an adverse drug reaction (ADR) belonging to the SOC nervous system (21%, 95% CI 18–24%), skin and subcutaneous (14%, 95% CI 11–17%), general (13%, 95% CI 10–17%) and gastrointestinal (8%, 95% CI 5–11%) disorders. Disease worsening was observed in 15.9% of the cases, mostly related to a lack of efficacy of the replacement drug. Half of the cases were considered as serious. Evolution was favourable in 79.4% of the cases. Death and/or life‐threatening situations were reported in 5.8% of the cases. Medication errors (MEs) were identified in 51 cases (11%), mostly occurring at the administration step and involving a human factor. Conclusion: This study emphasizes the clinical impact of drug shortage in terms of ADRs, ME and inefficiency. These observations underline the importance of a global health policy programme to limit the occurrence of drug shortages and to reinforce the information provided to patients and health care professionals in this context to limit risk.